Innovative methods to enhance transaction security of banking applications - Költzsch, Gregor (Journal of Business Economics and Management, 2006)
The increasing number of identity theft incidents such as credit card fraud, card duplication and internet attacks threaten the banking business that is mainly based on customer trust. Information and communication technologies create new business opportunities and innovative applications but do also enable new attack scenarios. Therefore, maintaining security and integrity is essential for the future economic success of banking. Biometric technologies such as fingerprint and facial recognition provide the means to enhance banking security. They are concerned with the measurement and evaluation of human physiological or behavioral data. Although the security‐oriented use of biometric technologies has become the most important field of development, they also enable a variety of convenience‐oriented use cases and applications. The article describes the security issues raised by technology‐based banking applications and outlines the idea of biometric technologies. Eventually, potential security and convenience‐driven use cases for biometrics in banking are illustrated based on examples given by a variety of professional project reports, magazines and other sources. Firstd Published Online: 14 Oct 2010